Sustainability status of amphidromous nike fish, postlarva Gobioidei, in estuarine water - F.M. Sahami; S.N. Hamzah; A.H. Tome; S.A. Habibie; M.R.U. Puluhulawa (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Nike fish are a postlarvae group of gobies found in the Gobiidae and Eleotridae families. These fish are a seasonal delicacy in Gorontalo, with significant economic value and popularity among the community. Data from 2020 to 2021 showed a downward trend in Nike fish production in Gorontalo City despite ongoing efforts to promote it as a consumable fish. Therefore, this study assessed the sustainability status of Nike fish in the waters of Tomini Bay Gorontalo.METHODS: This study was conducted across five Nike fishing locations in Tomini Bay, Gorontalo Province, namely the Bone-Bolango, Bilungala, Tombulilato, Taludaa, and Bilato estuaries, from April to September 2023. Data were collected through interviews with 109 Nike fishers and four experts from government agencies in Gorontalo Province. Meanwhile, other supporting data were obtained from various references that support the study objectives. The sustainability status analysis was conducted using rapid appraisal for fisheries, a software with an assessment method comprising five dimensions, ecological, economic, social, ethical, and technological, which are analyzed multi-dimensionally.FINDINGS: The results showed that of the five dimensions analyzed, only one, the technological dimension, exhibited sustainability. Meanwhile, the other four dimensions, including ecology, economic, social, and ethical, showed a less sustainable status. Some attributes that significantly affected the sustainability of Nike fish resource use in the waters of Tomini Bay, Gorontalo, include fishing location, Nike diversity, by-products, profit distribution, contribution to regional revenue, dependence on subsidies, level of conflict, the role of fishermen in terms of sustainability, fish landing sites, handling on board, externalities (waste disposal), and the level of violations. The results of the multi-dimensional scaling analysis showed that the average index values of the ecological, economic, social, and ethical dimensions are 33.53, 40.33, 30.86, and 25.19, respectively, demonstrating a less sustainable status. Meanwhile, only one of the five dimensions studied has an index value of more than 50—the technological dimension. The multi-dimensional scaling index value of the technology dimension is 84.09, demonstrating its sustainable status. The stress value (0.14 to 0.15) and the coefficient of determination (0.91 to 0.94) in the multi-dimensional scaling calculation showed that the analysis carried out was appropriate.CONCLUSION: The sustainability status of Nike fish in the waters of Tomini Bay, Gorontalo, is less sustainable and highly dependent on the environmental factors that support their life as amphidromous fish. The involvement of all stakeholder elements in implementing sustainable practices is also essential in terms of supporting sustainability. Therefore, this study provided important contributions that can be used by local governments and stakeholders to form appropriate management policies to ensure sustainability in the future. This study can provide information or insights for countries that have fishery potential similar to the waters of Tomini Bay, Gorontalo, to carry out better fisheries management.